The missing Myopus: plugging the gaps in Late Pleistocene small mammal identification in western Europe with geometric morphometrics. (2nd February 2021) - Arbez, Louis; Royer, Aurelien; Schreve, Danielle; Laffont, Remi; David, Serge; Montuire, Sophie
Abstract: Lemmus and Myopus are two lemming species with distinct habitat requirements but which show very similar dental morphologies. They are thus extremely difficult to distinguish from one another in the fossil record on the basis of their dental remains, leading to poor understanding of the palaeobiogeographical evolution of Myopus as well as inaccurate palaeoenvrionmental reconstructions. Currently, the presence of Myopus in the fossil register from the Pleistocene is still debated and no firm occurrence of this lemming in western Europe has yet been confirmed for the Late Pleistocene. In this paper, we used geometric morphometrics on modern material to establish morphological differences between Lemmus and Myopus teeth (first lower and third upper molars). Morphological data were then used to build a robust linear discriminant model able to confidently classify isolated teeth of these two genera, and finally, linear discriminant models were used on fossil remains of Lemmus/Myopus from two Late Pleistocene archaeological/palaeontological sites (Grotte des Gorges and Gully Cave). This study demonstrates, for the first time, the presence of Myopus schisticolor in west European Late Pleistocene sites between the end of Marine Isotope Stage 3 and the beginning of the Holocene, during climatic events that favoured the development of taiga forest of birch and pine in these regions.